Protein-Ligand Identification and In Vitro Inhibitory Effects of Cathine on 11 Major Human Drug Metabolizing Cytochrome P450s - Sharoen Lim, Yu Ming; Jason Loo, Siau Ee; Mustafa, Alshagga; Mohammed Abdullah, Alshawsh; Chin E., Ong; Yan, Pan (SAGE Publications Inc., 2022)
Cathine is the stable form of cathinone, the major active compound found in khat (Catha edulis Forsk) plant. Khat was found to inhibit major phase I drug metabolizing cytochrome P450 (CYP) enzyme activities in vitro and in vivo. With the upsurge of khat consumption and the potential use of cathine to combat obesity, efforts should be channelled into understanding potential cathine-drug interactions, which have been rather limited. The present study aimed to assess CYPs activity and inhibition by cathine in a high-throughput in vitro fluorescence-based enzyme assay and molecular docking analysis to identify how cathine interacts within various CYPs’ active sites. The half maximal inhibitory concentration (IC50) values of cathine determined for CYP2A6 and CYP3A4 were 80 and 90 μM, while CYP1A2, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1, CYP2J2 and CYP3A5 showed no significant inhibition. Furthermore, in Ki analysis, the Lineweaver-Burk plots depicted non-competitive mixed inhibition of cathine on both CYP2A6 and CYP3A4 with Ki value of 63 and 100 μM, respectively. Cathine showed negligible time-dependent inhibition on CYPs. Further, molecular docking studies showed that cathine was bound to CYP2A6 via hydrophobic, hydrogen and π-stacking interactions and formed hydrophobic and hydrogen bonds with active site residues in CYP3A4. Both molecular docking prediction and in vitro outcome are in agreement, granting more detailed insights for predicting CYPs metabolism besides the possible cathine-drug interactions. Cathine-drug interactions may occur with concomitant consumption of khat or cathine-containing products with medications metabolized by CYP2A6 and CYP3A4.